The Impact of Wheat Row Planting on Farmer’s Livelihoods, in Case of Wayu Tuka Woreda East Wollaga Zone, Oromia -Ethiopia - Lelisa Mamo Abdisa (Budapest International Research in Exact Sciences (BirEx) Journal, 2023)
The aim of the study was to saw the Impact of wheat row planting to on farmer’s livelihoods in case of Wayu Tuka Woerda in East Wollega Zone., Oromia Rgion, Ethiopia. Wheat crop planting is a highly valuable grain for Ethiopian people both in production and in consumption. The objective of the research was to investigate the impact of the adoption of wheat row planting on farmer livelihoods in study area. The study was based on cross sectional research which was included both qualitative and quantitative research approach. The data were collected from total 135 respondents selected from three kebels of Wayu Tuka Woerda by using random sampling method. From the total 135 respondents 82 were wheat row planting adopters while 53 were non wheat row planting adopters. Both primary and secondary data used and analysed using descriptive statistics, logit and propensity score matching model. The software used for data entry and analysis were STATA14.2. The results show that about 61% of the respondents are users of wheat row planting whereas 39% can be classified as non-adopters of wheat row planting. The empirical Results revealed that the overall impact evaluation of the study by Propensity Score Matching shows that the average yield output of the participant groups on wheat row planting farm exceeds livelihoods of the non-adopter group by 19,626.18 ETB. Finally, wheat row planting has significant impact on farmer’s livelihoods increment. It is better to encourage farmer households as they actively participant in wheat row planting technology and support them by giving training, supplying agricultural inputs and adopting new technology for them with adequate skills for enhancing their annual livelihoods and development of the country economy.